MANUSIA DALAM AL-QUR’AN (STUDI ATAS KITAB MAQÂL FÎ AL-INSÂN: DIRÂSAH QUR’ANIYYAH KARYA ‘Â’ISYAH ‘ABD AL-RAHMAN BINT AL-SYATHI’) - Jannah, Miftahul (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2017)
This article examines about the exposure of human in the Qur?an according to ?Â?isyah ?Abd al-Rahman Bint al-Syathi?. The object of this examination is her book of Maqâl fî al-Insân, and explained with thematic method. Actually, the book focused on human things. The author wants to apply one strict specific method to investigate how al-Qur?an uses several terms that refer to ?human? word, such as al-Basyar, al-Insân dan al-Ins. Here, Bint al-Syathi? tried to distinguish the meanings of those terms, which are often considered synonims, even almost all of dictionaries or books of exegesis in the classical tradition confirm these synonyms. However, she rejected the concept because the original Arabic tradition also rejected it. In her opinion, the Qur?an itself provided a very real representation and distinguished between the three conceptions.